Analysis of reproducibility and robustness of OrganoPlate® 2-lane 96, a liver microphysiological system for studies of pharmacokinetics and toxicological assessment of drugs. (December 2022) - Kato, Yuki; Lim, Alicia Y.; Sakolish, Courtney; Valdiviezo, Alan; Moyer, Haley L.; Hewitt, Philip; Bajaj, Piyush; Han, Gang; Rusyn, Ivan
Abstract: Establishing the functionality, reproducibility, robustness, and reliability of microphysiological systems is a critical need for adoption of these technologies. A high throughput microphysiological system for liver studies was recently proposed in which induced pluripotent stem cell-derived hepatocytes (iHeps) and non-parenchymal cells (endothelial cells and THP-1 cells differentiated with phorbol 12-myristate 13-acetate into macrophage-like cells) were co-cultured in OrganoPlate® 2-lane 96 devices. The goal of this study was to evaluate this platform using additional cell types and conditions and characterize its utility and reproducibility. Primary human hepatocytes or iHeps, with and without non-parenchymal cells, were cultured for up to 17 days. Image-based cell viability, albumin and urea secretion into culture media, CYP3A4 activity and drug metabolism were assessed. The iHeps co-cultured with non-parenchymal cells demonstrated stable cell viability and function up to 17 days; however, variability was appreciable both within and among studies. The iHeps in monoculture did not form clusters and lost viability and function over time. The primary human hepatocytes in monoculture also exhibited low cell viability and hepatic function. Metabolism of various drugs was most efficient when iHeps were co-cultured with non-parenchymal cells. Overall, we found that the OrganoPlate® 2-lane 96 device, when used with iHeps and non-parenchymal cells, is a functional liver microphysiological model; however, the high-throughput nature of this model is somewhat dampened by the need for replicates to compensate for high variability. Highlights: Microphysiological systems are thought to be more human-relevant models for toxicology. Liver microphysiological systems are complex devices that typically have low throughput. This study tested a higher-throughput liver microphysiological system for its robustness. OrganoPlate® 2-lane 96 plates are most functional with iHeps and non-parenchymal cells. This model needs high number of replicates to deliver robust results limiting throughput.